SUBSURFACE MODELING ON âRFPâ GEOTHERMAL FIELD USING 3-D SEISMIC TOMOGRAPHY FROM FEBRUARY TO MAY 2016 - Fitra Perdana, Rahman
The "RFP" Geothermal Field is one of the geothermal fields that has been operating with a total energy produced of 227 MWe and located 40 km south of Bandung City. Geothermal activities induced microearthquakes, hence an additional research is essential to examine the subsurface state. Many studies have been carried out to observe conditions under the surface. One method that is quite effective is 3-D seismic tomography because it can determine the condition of subsurface fluid saturation. Therefore, this study aims to determine the state of "RFP" geothermal field by using more accurate hypocenter relocation and 3-D seismic tomography. In this research, 448 microearthquakes recorded during the period of February to May 2016. Then, the microearthquakes data is used to find out the initial hypocenter location using Geiger Adaptive Damping. We determine the hypocenter relocation by cross-correlating the waveform and double-difference method. The results of the relocation will be the input for determining 1-D linear velocity models and 3-D seismic speed models. Relocated hypocenter indicates that earthquakes in this area occur due to injection wells and production wells. Tomographic results show that there are several velocities that has a high contrast in 1 km depth and interpreted to be associated with ancient volcanic deposits and intrusion. The anomaly values of Vp, Vs, and Vp / Vs indicate that there is a steam saturated zone in the north and a water saturated zone in the south. In addition, there is also a chemical reaction that hamper the fluid flow from the south to the northern part.